Konstruk Ideologi Muhammadiyah: Fondasi Pengembangan Instrumen Pengukuran Kekuatan Ideologi Muhammadiyah - Joko Subando; Muh Samsuri; Edy Muslimin (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to find out the construct of Muhammadiyah ideology. This research was categorized as qualitative research with literature review as a method of data collection. The data consisted of the concept and the understanding related to Muhammadiyah ideology, the source of data was books and journals examining Muhammadiyah ideology from the aspect of outlook on life, life guidelines of Muhammadiyah citizens and Muhammadiyah strategies in realizing their ideals of life. Data analysis techniques used a simplified approach. The results show that the Muhamadiyah Ideology is a set of understandings that contain muhammadiyah views, life guidelines and strategies in realizing his ideals of life. Muhammadiyah's view of life is reflected in the muqaddimah of Muhammadiyah's articles of association containing views on anchorage, community, views on Islamic teachings, enforcement of Islamic teachings, ittiba' nabi in struggle, views of organization and muhammadiyah ideals. The life guidelines of Muhammadiyah residents discuss self-guidelines in religion, socializing in society, organizing and guidelines for state life. There are several Muhammadiyah strategies in realizing their life ideals pursued by community development related to aqidah, worship and morals, improving the quality of life of the community, fostering Muhammadiyah cadres, strengthening Muhammadiyah associations and appropriate political and state strategies. Furthermore, the ideological construct can be used as a foundation in the development of instruments for measuring the strength of Muhammadiyah ideology.